2022
DOI: 10.1080/15548627.2022.2046448
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 -activated accelerating effect of LINC00941/lncIAPF on fibroblast-to-myofibroblast differentiation by blocking autophagy depending on ELAVL1/HuR in pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by lung scarring and has no effective treatment. Fibroblast-to-myofibroblast differentiation and myofibroblast proliferation and migration are major clinical manifestations of this disease; hence, blocking these processes is a practical treatment strategy. Here, highly upregulated LINC00941/lncIAPF was found to accelerate pulmonary fibrosis by promoting fibroblast-to-myofibroblast differentiation and myofibroblast proliferation and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 61 publications
4
22
0
Order By: Relevance
“…The receiver operating characteristic curve (ROC) between lncIAPF and FVC shows that the sensitivity and specificity values are 87.5% and 75.0% in patients with IPF, respectively. The area under the ROC curve is 0.879 ( Zhang J et al, 2022 ). In this study, we further proved that the lncIAPF–HuR complex can be a target related to autophagy for drug action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The receiver operating characteristic curve (ROC) between lncIAPF and FVC shows that the sensitivity and specificity values are 87.5% and 75.0% in patients with IPF, respectively. The area under the ROC curve is 0.879 ( Zhang J et al, 2022 ). In this study, we further proved that the lncIAPF–HuR complex can be a target related to autophagy for drug action.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that DME weakened HuR stability to promote autophagy via inhibiting lncIAPF stability and transcription. The collected evidence indicates that overexpression or mutation of EZH2, STAT1, and FOXK1 is closely related to the occurrence and poor prognosis of multiple diseases; thus, they are attractive therapeutic targets for the treatment of diseases ( Bowman et al, 2014 ; Kong et al, 2020 ; Patoli et al, 2020 ; Zhang J et al, 2022 ). Our mechanistic dissection revealed that DME inhibits EZH2, STAT1, and FOXK1 to block autophagy flux via weakening lncIAPF–HuR complex stability.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that LINC00941 plays a role in regulating the differentiation of keratinocytes ( 100 ). Another recent study found that upregulated LINC00941 is associated with idiopathic pulmonary fibrosis (IPF), which is an incurable and progressive disease characterized by lung scarring ( 101 ). In IPF, LINC00941 was found to promote the differentiation of fibroblasts as well as increase cell proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, lncIAPF forms a RNA-protein complex with human antigen R (HuR) to block autophagy by controlling the stability of the target genes EZH2 (enhancer of zeste 2 polycomb repressive complex 2 subunit), STAT1 (signal transducer and activators of transcription 1) and FOXK1 (forkhead box K1). Zhang et al have provided preclinical evidence from the mouse models of lung fibrosis and patient samples and proposed pharmacological approaches for inhibiting lncIAPF related to autophagy; these approaches represent promising therapeutic options for IPF ( Zhang et al, 2022 ). However, numerous questions need to be answered.…”
Section: Senescent Aeciis Promote Idiopathic Pulmonary Fibrosis Devel...mentioning
confidence: 99%